Pengembangan Aplikasi Pengelolaan Rekam Medis Obgin berbasis Web (Studi Kasus : Rumah Sakit Umum Daerah Kota Malang) - Ibnu Rakha; Agi Putra Kharisma; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Obstetrics and Gynecology Medical Record Manager application is a system aimed at doctors and midwives to help manage obstetric patient data along with storing medical records of patients who have already performed examinations. In the patient examination process, doctors and midwives carry out initial assessments and patient medical assessments. The assessment consists of a physical examination, examination of vital signs, history taking, and diagnosis as well as follow-up that must be done. Doctors and midwives will fill the patient's needs during hospitalization consisting of elimination needs, fluid needs and rest needs. This application takes a case study at the Malang City Regional Hospital. development of obgin medical record application which begins with the analysis stage to the testing stage with an object oriented approach. Obtained 74 functional requirements and 1 non-functional requirements. At the implementation stage using laravel. In unit testing, 3 test cases were taken with 100% valid results. Validation testing was tested on 74 test cases obtaining 100% valid results. Compatibility testing was tested on 2 different browsers, devices, and operating systems with the results running smoothly.